Se-Doping Activates FeOOH for Cost-Effective and Efficient Electrochemical Water Oxidation - Niu, Shuai; Jiang, Wen-Jie; Wei, Zengxi; Tang, Tang; Ma, Jianmin; Hu, Jin-Song; Wan, Li-Jun (Journal of the American Chemical Society, 2019)
Ni or Co is commonly required in efficient electrocatalysts for oxygen evolution reaction (OER). Although Fe is much more abundant and cheaper, full-Fe or Fe-rich catalysts suffer from insufficient activity. Herein, we discover that Se-doping can drastically promote OER on FeOOH and develop a facile on-site electrochemical activation strategy for achieving such a Se-doped FeOOH electrode via an FeSe precatalyst. Theoretical analysis and systematic experiments prove that Se-doping enables FeOOH as an efficient and low-cost OER electrocatalyst. By optimizing the electrode structure, an industrial-level OER current output of 500 mA cm–2 is secured at a low overpotential of 348 mV. The application of such an Fe-rich OER electrode in a practical solar-driven water splitting system demonstrates a high and stable solar-to-hydrogen efficiency of 18.55%, making the strategy promising for exploring new cost-effective and highly active electrocatalysts for clean hydrogen production.